If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3q + -8 = 4q Reorder the terms: -8 + 3q = 4q Solving -8 + 3q = 4q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-4q' to each side of the equation. -8 + 3q + -4q = 4q + -4q Combine like terms: 3q + -4q = -1q -8 + -1q = 4q + -4q Combine like terms: 4q + -4q = 0 -8 + -1q = 0 Add '8' to each side of the equation. -8 + 8 + -1q = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1q = 0 + 8 -1q = 0 + 8 Combine like terms: 0 + 8 = 8 -1q = 8 Divide each side by '-1'. q = -8 Simplifying q = -8
| -4t=-8t-12 | | -3v=2-3v | | 20x-36*-20=-6 | | -15+7y=25+2y | | 15x=345 | | 5(n+3)-7=23 | | 15x=355 | | 12(x^2-15x+40)=0 | | -7-6=8 | | 13x+7(-3*-1)=-63 | | 2t-7= | | 10x+48=180 | | X+y=480 | | 2(2x-4)-2=2(x-5)+4 | | 3x+20=2x+11 | | 7t+5=5t+7 | | 7=b-4 | | -5n^2+3n+224=0 | | 2x+y=480 | | 13x=5x+48 | | 2y-4=10y+36 | | 4b-3=3b+9 | | 2(x^2+60x-200)=0 | | 14x+8=6x+12 | | 2x^5-32=0 | | 2(6x-4)=27 | | log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d | | cos(x)=-3.8 | | 3x-61= | | X^2-14x+17=-6x+2 |